Menghadapi Tantangan Digital: Kolaborasi Antara E-Commerce Dan E-Business - Nasution, Muhammad Haviz (EL-EMIR Institute, 2025)
This study aims to analyze the collaboration between e-commerce and e-business in facing increasingly complex digital challenges. In today's digital era, companies are required to integrate technology to optimize operations, improve efficiency, and create a better customer experience. Although e-commerce and e-business have different focuses, namely online transactions and the entire business process, collaboration between the two can create synergies that support business sustainability and growth. This study uses a library approach to explore the benefits, challenges, and strategies for effective collaboration between e-commerce and e-business. The results of the study show that this collaboration allows companies to expand their markets, utilize customer data for decision making, and improve operational efficiency. However, challenges such as data security, adaptation to new technologies, and increasingly fierce competition need to be addressed with the right strategy. This study also provides suggestions for business actors to improve digital literacy, adopt relevant technology, and maintain data security. For the government, it is recommended to provide better digital infrastructure and support regulations that facilitate innovation.